Implementasi Strategi Pemasaran UMKM Pempek Palembang FC Melalui Media Sosial Instagram - Daniel Antonius Wijaya; Devita Sari; Astriani Astriani; Aidil Ramadhani; Dian Renita Andiani; David Fernando; Tiara Fitari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to implement the marketing strategy of Pempek Palembang FC (Micro, Small, and Medium Enterprises) MSMEs through Instagram social media. Established in May 2022 in Bangka Belitung, Pempek Palembang FC offers Palembang specialty food products, namely pempek and tekwan. Despite its high market potential, this MSME faces serious challenges due to its lack of social media presence, resulting in limited marketing reach. This research used qualitative methods with interviews and observations to explore the problems and solutions faced. The results show that the creation of social media accounts, creative content development, and consistency in uploading can increase visibility and sales. Through digital marketing strategies, Pempek Palembang FC can reach a wider market, build a customer community, and increase competitiveness in the digital era. Keywords: Pempek Palembang FC, MSME, marketing strategy, social media, Instagram, digital marketing.